Effect of glycerine on drying of cut foliage of silver oak (Grevillea robusta) (Current Horticulture, 2024)
The study aimed to evaluate the impact of glycerine on the drying process of cut foliage from silver oak (Grevillea robusta).  Two methods of glycerinisation, namely uptake and full dip, were used, and different concentrations of glycerine (10%, 20%,  and 40%) were tested. The overall acceptability of the dried foliage was assessed, with a higher score indicating better quality.  The results showed that the full dip method achieved the highest score for overall acceptability (3.36) compared to the uptake  method. Among the different concentrations of glycerine, 40% was identified as the optimum concentration for the drying  process. The maximum score obtained for overall acceptability of the dried foliage was 4.98, indicating a relatively high level of  satisfaction with the quality. Overall, the study suggests that using the full dip method and a glycerine concentration of 40% can  result in dried foliage with good overall acceptability. These findings can be useful for improving the drying process of silver  oak foliage and enhancing its quality for various applications.
Keywords: Glycerinisation; Dry flowers; Brittleness